Upgraded ESRF BM29 beamline for SAXS on macromolecules in solution. (17th May 2013) - Pernot, Petra; Round, Adam; Barrett, Ray; De Maria Antolinos, Alejandro; Gobbo, Alexandre; Gordon, Elspeth; Huet, Julien; Kieffer, Jerôme; Lentini, Mario; Mattenet, Muriel; Morawe, Christian; Mueller‐Dieckmann, Christoph; et al.
<x xml:space="preserve">Abstract</x> Small‐angle X‐ray scattering (SAXS) measurements of proteins in solution are becoming increasingly popular with biochemists and structural biologists owing to the presence of dedicated high‐throughput beamlines at synchrotron sources. As part of the ESRF Upgrade program a dedicated instrument for performing SAXS from biological macromolecules in solution (BioSAXS) has been installed at the renovated BM29 location. The optics hutch has been equipped with new optical components of which the two principal elements are a fixed‐exit double multilayer monochromator and a 1.1 m‐long toroidal mirror. These new dedicated optics give improved beam characteristics (compared with the previous set‐up on ID14‐3) regarding the energy tunability, flux and focusing at the detector plane leading to reduced parasitic scattering and an extended s‐range. User experiments on the beamline have been successfully carried out since June 2012. A description of the new BioSAXS beamline and the set‐up characteristics are presented together with examples of obtained data.